الحجامة دراسة حديثيّة فقهيّة معاصرة - دغمان, سعيدة (University of Eloued-جامعة الوادي, 2015)
This research entitled “Cupping, Hadith and contemporary jurisprudence viewpoint modern study”, included an introduction, three sections and a conclusion. The main problematic of this research is to prove the existing relationship between the modern cupping and the prophetic cupping, as well as its implications. The first section included a definition of cupping, a historical overview, its types, the different listed reasons of the people reluctance to refrain of dealing with it, as well as then its suddenly reappear. At the second section, I showed the benefits of cupping mentioned in the light of Sunnah according to the epoch, the diseases, its places, and times. Finally, at the third section I tried to gather some indications of the scientists and their evidence in contentious cupping jurisprudence, with a statement of the doctrines of scientists and their evidences, discussed and likely to give an opinion the more preponderant. At the conclusion of this research, I reported the most important findings, and some recommendations that have not be mentioned in the other researches. The core result and recommendation are: 1. Cupping of the Prophet was been considered as an alternative treatment in comparison to the old one, but actually, it is also considered as the same modern cupping. 2. The concerned authorities must consider cupping as a complementary treatment to the modern medicine.
مذكرة ماستر
Keywords: مسائل فقهية /الحجامة/السنة النبوية; Doctrinal issues / cupping / Sunnah